2007
DOI: 10.1096/fasebj.21.5.a131
|View full text |Cite
|
Sign up to set email alerts
|

Control of Interferon‐alphaA by CD73: Implications for Mucosal Inflammation

Abstract: Inflammatory diseases change tissue metabolism, resulting in alterations in extracellular adenine nucleotide regulation and a resultant protective influence of adenosine (Ado). We hypothesized that Ecto‐5′‐nucleotidase (CD73), a central surface enzyme in the generation of extracellular Ado, is protective in mucosal inflammation as modeled by TNBS colitis. Initial studies revealed a greater than 3‐fold increase in CD73 mRNA levels following induction of TNBS colitis. We further demonstrate more severe colitis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…These observations complete previous studies showing that mice lacking CD73 displayed increased colonic inflammation. 3,37 Our data using CD4-cre TGF-bRII lox/lox mice and vitamin A-deficient mice indicate that TGF-b and RA synergize to induce CD73 expression in Tconvs, whereas RA is dispensable for CD73 expression by Tregs. The source of RA is probably related to the population of CD103 þ dendritic cells in the LP 38,39 and to the MLN dendritic cells and stromal cell expressing aldh1a2, 40 a retinal dehydrogenase involved in the conversion of retinal into RA.…”
Section: Discussionmentioning
confidence: 90%
“…These observations complete previous studies showing that mice lacking CD73 displayed increased colonic inflammation. 3,37 Our data using CD4-cre TGF-bRII lox/lox mice and vitamin A-deficient mice indicate that TGF-b and RA synergize to induce CD73 expression in Tconvs, whereas RA is dispensable for CD73 expression by Tregs. The source of RA is probably related to the population of CD103 þ dendritic cells in the LP 38,39 and to the MLN dendritic cells and stromal cell expressing aldh1a2, 40 a retinal dehydrogenase involved in the conversion of retinal into RA.…”
Section: Discussionmentioning
confidence: 90%
“…As proof of principle for the relevance of ␤1-integrin induction in vivo, we investigated ITGB1 expression in the TNBS murine model of colitis, a model we have previously shown to result in severe ulceration and concomitant tissue hypoxia (25). Moreover, as an extension of our previous work (21) implicating PHD inhibition and enhanced reepithelialization of colitic wounds (Fig.…”
Section: Itgb1 Is Induced In a Murine Model Of Colitismentioning
confidence: 93%
“…The transcriptional profile of T84 epithelial cells subjected to control (normoxia, pO 2 147 torr) or hypoxia (pO 2 20 torr for 6 or 18 h hypoxia) was assessed from total RNA using quantitative genechip expression arrays (Affymetrix, Santa Clara, CA, USA) (25). Results obtained by gene array analysis were subsequently verified in 18CO human fibroblast cells by real-time polymerase chain reaction (PCR) (ITGB1 primer set: forward, 5Ј-CCTTGG-GATGACTTGATTG-3Ј; reverse, 5Ј-ACCTTTCGGTCACTTAG-GG-3Ј) using iQ SYBR mix (iCycler; Bio-Rad, Hercules, CA, USA), as described previously (25,26).…”
Section: Transcriptional Analysismentioning
confidence: 99%
“…However, a seminal paper from our lab provides some evidence linking HIF1-dependent CD73 expression and type I IFN production in inflamed intestinal tissues. Gene array profiling performed on colonic mucosal scrapings of CD73-/-vs. wild-type mice revealed a loss of IFNαA expression in the absence of CD73 [25]. It appears that while type I IFNs induce CD73 expression, the activity of CD73, in turn, functions in a feed-forward manner to drive IFNαA expression.…”
Section: Cd73 Ifnαa and Colitismentioning
confidence: 95%
“…Meanwhile, additional reports of studies in murine models of colitis have indicated a protective role for the Ado A3R [23,24]. Thus, lack of Ado in a setting of intestinal inflammation may be detrimental and, indeed, as it was shown in CD73-/-mice impaired in Ado production, the absence of Ado leads to exacerbation of colitis [25].…”
Section: Ado Signalingmentioning
confidence: 99%